Intra‐ and inter‐individual variability in the mechanical properties of the human skin from in vivo measurements on 20 volunteers. Issue 4 (30th March 2017) - Jacquet, E.; Chambert, J.; Pauchot, J.; Sandoz, P.
Abstract : Background/purpose: The mechanical properties and behavior of the human skin in vivo are of medical importance, particularly to surgeons who have to consider the skin extension capabilities in the preparation of surgical acts. Variable data can be found in literature that result from diverse kinds of tests (in vivo, ex vivo, and postmortem) performed with different instruments. Methods: This paper presents the results of in vivo measurements performed on a cohort of 20 healthy volunteers with an ultralight homemade uniaxial extensometer. Different anatomical zones were explored under different directions of solicitation in order to document inter‐ and intra‐individual variability as well as skin anisotropy. Results: The experimental data obtained are fitted with a phenomenological exponential model allowing the identification of three parameters characteristic of the tested skin behavior. These parameters can be related to the concept of skin extensibility used by surgeons. Conclusion: The inter‐ and intra‐variability observed on that cohort confirms the need for a patient‐specific approach based on the in vivo measurement of the mechanical behavior of the human skin of interest. Even the direction of higher skin stiffness is found to be individual‐dependent. The capability of the extensometer used in this study to fulfill such measurement needs is also demonstrated.